Sarcoptic mange in the Scandinavian wolf Canis lupus population - Fuchs, Boris; Zimmermann, Barbara; Wabakken, Petter; Bornstein, Set; Månsson, Johan; Evans, Alina; Liberg, Olof; Sand, Håkan; Kindberg, Jonas; Ågren, Erik; Arnemo, Jon (BioMed Central Ltd., 2016)
Abstract Background Sarcoptic mange, a parasitic disease caused by the mite Sarcoptes scabiei, is regularly reported on wolves Canis lupus in Scandinavia. We describe the distribution and transmission of this parasite within the small but recovering wolf population by analysing 269 necropsy reports and performing a serological survey on 198 serum samples collected from free-ranging wolves between 1998 and 2013. Results The serological survey among 145 individual captured Scandinavian wolves (53 recaptures) shows a consistent presence of antibodies against sarcoptic mange. Seropositivity among all captured wolves was 10.1 % ( CI. 6.4 %–15.1 %). Sarcoptic mange-related mortality reported at necropsy was 5.6 % and due to secondary causes, predominantly starvation. In the southern range of the population, seroprevalence was higher, consistent with higher red fox densities. Female wolves had a lower probability of being seropositive than males, but for both sexes the probability increased with pack size. Recaptured individuals changing from seropositive to seronegative suggest recovery from sarcoptic mange. The lack of seropositive pups (8–10 months, N = 56) and the occurrence of seropositive and seronegative individuals in the same pack indicates interspecific transmission of S. scabiei into this wolf population. Conclusions We consider sarcoptic mange to have little effect on the recovery of the Scandinavian wolf population. Heterogenic infection patterns on the pack level in combination with the importance of individual-based factors (sex, pack size) and the north–south gradient for seroprevalence suggests low probability of wolf-to-wolf transmission of S. scabiei in Scandinavia.